Fractional order dynamical systems and its applications - Tenreiro Machado, J. A. (2019)
This article illustrates several applications of fractional calculus (FC) in science and engineering. It has been recognized the advantageous use of this mathematical tool in the modeling and control of many dynamical systems. In this perspective, this paper investigates the use of FC in the following fields:  Controller tuning;  Electrical systems;  Traffic systems;  Digital circuit synthesis;  Evolutionary computing;  Redundant robots;  Legged robots;  Robotic manipulators;  Nonlinear friction;  Financial modeling.